On the emergence of autism: neuroimaging findings from birth to preschool. (April 2013) - Wolff, Jason J; Piven, Joseph
SUMMARY  By definition, autism spectrum disorder (ASD) emerges early in life. Core clinical symptoms generally appear after a child's first birthday, and most children receive a diagnosis by the age of 4 years. This relatively narrow window of birth to age of onset affords the opportunity to chart the neurodevelopmental processes that give rise to ASD. Although much remains unknown, magnetic resonance brain imaging studies centered around the emergence of the disorder have yielded important clues about its pathogenesis. Prominent findings include evidence of increased cortical gray and white matter volumes, increased amygdala volumes, aberrant structural and functional connectivity, and atypical neurodevelopmental trajectories. Findings to date suggest a disrupted pattern of early brain development during an interval typically characterized by dramatic experience-dependent neurobehavioral development. Developmentally informed neuroimaging studies of ASD have the potential to improve our knowledge pertaining to etiology and early intervention.